2009
DOI: 10.4067/s0718-16202009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cladosporium echinulatum in carnation using bicarbonates and Trichoderma

Abstract: At the present time, fl oriculture occupies 2,124 ha, of which 180 ha are devoted to carnations. Almost all carnations produced are sold in the domestic market. Several diseases affect carnations, among them fairy-ring leaf spot (Cladosporium echinulatum), the most important foliar disease in Chile. Different control alternatives for fairy-ring spot were evaluated on the carnation cv. Sarinah in terms of disease incidence and severity. The study was performed in June-August 2003 with a commercial carnation pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Apart from the report of Sandoval et al 5 , no study has so far been reported for the management of fairy ring spot of carnations. According to the present results, Bacillus species with diverse AMP genes are good for the control of fairy ring spot of carnation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Apart from the report of Sandoval et al 5 , no study has so far been reported for the management of fairy ring spot of carnations. According to the present results, Bacillus species with diverse AMP genes are good for the control of fairy ring spot of carnation.…”
Section: Discussionmentioning
confidence: 93%
“…In India the pathogen was first identified in Himachal Pradesh 4 . Till now there is only one report for the management of fairy ring spot 5 . The study reported that sodium bicarbonate and T. virens was effective in reducing disease incidence.…”
mentioning
confidence: 99%
“…Bio-control agents such as C. globosum, G. catenulatum, T. harzianum, B. subtilis, and P. fluorescens have the ability to control cladosporium leaf spots (Huang 1978;Xiao and Li. 2013;Sandoval, et al, 2009 andWang et al, 2018) and enhance the plant growth (Compant et al, 2005).…”
mentioning
confidence: 99%